Tracing the Principle of Balance in Contractual Relationships Betwwen Customers and Indihome Sercvice Providers - Arief Nur Amrizal Mooduto (Universitas Negeri Gorontalo, 2020)
This research is intended to see and find out how the principle of balance between customers and Indihome service providers in the City of Gorontalo. This research uses empirical legal research methods, where facts and events on the ground are used as the main ingredient in determining the truth of the research. The data source used is the primary data source as the main data, and the secondary data source as supporting data consisting of documents and scientific work related to the problem being discussed. The sample (respondents) used in this study is the people of Gorontalo City who are customers of Indihome products and the second is the pewakilan from PT. Telkom Gorontalo Branch as indihome service provider. The results showed that the application of the principle of balance between customers and Indihome service providers in the City of Gorontalo was carried out jointly by the customer and the Indihome service provider. The customer applies the principle of balance by paying internet bills in accordance with the duration of time given. Indihome service providers apply the principle of balance by compensating, repairing networks, and other actions deemed necessary.